Housing Policy Reforms in Post Socialist Europe - Tsenkova, Sasha (Springer, 2017)
The book provides unique insights into the process of housing reforms in post-socialist Europe during its transition to markets and democracy. It explores the relationships between housing policy and housing system performance in nine countries: Albania, Bulgaria, Bosnia and Herzegovina, Croatia, Former Yugoslav Republic of Macedonia, Romania, Republic of Moldova, Serbia and Montenegro. The research captures important housing policy and market dynamics producing tangible outcomes of the transition processes. Using a comparative framework for analysis and evaluation, the book provides an enduring and sound illustration of the post-socialialist experience highlighting patterns of diversity, complexity and institutional transformation in the new path-dependent housing systems in the region. The research is driven by the premise that housing policy matters and that better policies lead to more efficient housing system performance.